The application of the principle al-‘Ibrah bi ‘Umūm al-Lafẓ in al-Qurṭubī’s Tafsīr: An analysis of legal verses - Yoga Perdana Kusuma; Abdul Munzir; Hidayatullah Ismail (Priviet Social Sciences Journal, 2025)
The Qur’an, as a guide for all humankind in various aspects of life and as a text with profound breadth of meaning, demands great caution in its interpretation. For this reason, Qur’anic exegesis (tafsir) has developed as a distinct discipline that functions to bridge human understanding with the divine messages contained in the Qur’an itself. One of the important principles in the tradition of Qur’anic exegesis is “al-‘ibrah bi ‘umūm al-lafẓ lā bi khuṣūṣ al-sabab.” This principle holds a central position because it ensures that the meaning of Qur’anic verses is not restricted by their specific occasions of revelation (asbāb al-nuzūl) but remains universally applicable across space and time. One of the exegetes widely known for the strength of his interpretations of Islamic law is al-Qurṭubī, through his tafsir work al-Jāmi‘li Aḥkām al-Qur’ān. However, the extent to which al-Qurṭubī consistently applies this principle has been rarely examined. Therefore, this study aims to analyze the application of the principle al-‘ibrah bi ‘umūm al-lafẓ lā bi khuṣūṣ al-sabab in al-Qurṭubī’s tafsir, particularly in relation to legal verses. This study employed a qualitative descriptive design with a library research approach. The primary data source is the classical tafsir al-Jāmi‘ li Aḥkām al-Qur’ān by al-Qurṭubī, while the secondary data consist of supporting literature such as other tafsir works, books on ‘ulūm al-Qur’ān, uṣūl al-fiqh, asbāb al-nuzūl, and studies on tafsir methodology. The findings of this study indicate that al-Qrṭbī is consistent in implementing this principle, in that he does not treat the specificity of the occasion of revelation as a limitation of the legal ruling. In contrast, he takes the generality of the wording of the verse as the main basis for establishing shar‘ī rulings, so that the resulting laws are universal and transcend their historical context, as seen in the cases of polygamy, the penal code for theft, and ẓihār.